MicroRNA-181a regulates IFN-γ expression in effector CD8+ T cell differentiation - Amado, Tiago (2020)
CD8+ T cells are key players in immunity against intracellular infections and tumors. The main cytokine associated with these protective responses is interferon-γ (IFN-γ), whose production is known to be regulated at the transcriptional level during CD8+ T cell differentiation. Here we found that microRNAs constitute a posttranscriptional brake to IFN-γ expression by CD8+ T cells since the genetic interference with the Dicer processing machinery resulted in the overproduction of IFN-γ by both thymic and peripheral CD8+ T cells. Using a gene reporter mouse for IFN-γ locus activity, we compared the microRNA repertoires associated with the presence or absence of IFN-γ expression. This allowed us to identify a set of candidates, including miR-181a and miR-451, which were functionally tested in overexpression experiments using synthetic mimics in peripheral CD8+ T cell cultures. We found that miR-181a limits IFN-γ production by suppressing the expression of the transcription factor Id2, which in turn promotes the Ifng expression program. Importantly, upon the MuHV-4 challenge, miR-181a-deficient mice showed a more vigorous IFN-γ+ CD8+ T cell response and were able to control viral infection significantly more efficiently than control mice. These data collectively establish a novel role for miR-181a in regulating IFN-γ-mediated effector CD8+ T cell responses in vitro and in vivo.